Time and band limiting for matrix valued functions: An integral and a commuting differential operator - Grünbaum, Alberto (2017)
The problem of recovering a signal of finite duration from a piece of its Fourier transform was solved at Bell Labs in the 1960's, by exploiting a 'miracle': a certain naturally appearing integral operator commutes with an explicit differential one. Here we show that this same miracle holds in a matrix valued version of the same problem.